Effect of Type and Concentration of Acid on Chemical Characteristics of Mexican Petunia (Ruellia simplex C. Wright) Flower Extract - Ulya Sarofa; Sindy Puspitasari; Rosida (Future Science, 2024)
Mexican petunia (Ruellia simplex C. Wright) is a flowering plant which has blue to purple flowers which are thought to be anthocyanin components. The solvent used in the extraction of Mexican petunia flowers is distilled water which is a polar solvent with the addition of functional acids in order to denature plant cells so that maximum anthocyanin is extracted. The aim of this research was to determine the effect of acid treatment type and concentration on chemical characteristics of Mexican petunia flower extract and knowing its stability to pH, temperature and heating time for the best treatment. This study used a completely randomized factorial design with two factors, namely the first factor was the type of acid (acetic acid and citric acid) and the second factor was the acid concentration (0.05%; 0.1%; 0.15% ; 0.2%). The data obtained were analyzed using ANOVA next treatments that had a significant effect were tested further using the DMRT test at the 5% level. The best results were obtained in citric acid treatment with a concentration of 0.2% with initial pH 2.04, final pH 2.95, color intensity 0.412, and total anthocyanin 0.0728%, stable at acidic pH in the range of pH 3, heating temperature up to 60OC and heating time up to 60 minutes.